Effectiveness of Platelet Rich Plasma and Bone Graft in the Treatment of Intrabony Defects: A Clinico-radiographic Study - Jalaluddin, Mohammad (Open Dent J, 2018)
BACKGROUND & OBJECTIVES: Periodontal disease is characterized by the presence of gingival inflammation, periodontal pocket formation, loss of connective tissue attachment and alveolar bone around the affected tooth. Different modalities have been employed in the treatment and regeneration of periodontal defects which include the use of bone grafts, PRP and other growth factors.The purpose of this prospective, randomized controlled study was to compare the regenerative efficacy of PRP and bonegraft in intrabony periodontal defects. METHODOLOGY: This randomized control trial was carried out in the Department of Periodontics & Oral Implantology, Kalinga Institute of Dental Sciences and Hospital, KIIT University, Bhubaneswar. The study sample included 20 periodontal infrabony defects in 20 patients, 12 males and 8 females. The patients were aged between 25 -45 years(with mean age of 35 years). The 20 sites selected for the study were was randomly divided into 2 groups of 10 sites each. Group A: PRP alone, Group B: Bone Graft. STATISTICAL ANAYSIS & RESULTS: STATISTICAL ANALYSIS WAS DONE USING SPSS (VERSION 18.0): Statistical analysis was done usingpaired ‘t’ tests and ANOVA that revealed a significant reduction ingingival index, plaque index, probing pocket depth and gain in clinical attachment level at various time intervalswithin both the groups. Radiographic evaluation revealed statistically significant defect fill (p<0.001) at the end of 6months within both the groups. However, there was astatistically significant difference seen in group B radiographically, when compared to group A. CONCLUSION: Both the groups showed promising results in enhancing periodontal regeneration; however the resultswith bonegraftwere comparatively better, although not statistically significant when compared to PRP alone.